2017
DOI: 10.20344/amp.8681
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the ‘Decline’ of Dental Student Empathy within the Course in Latin America

Abstract: Introduction:The controversy over the presence of empathic decline within the course in students of medicine, dentistry and health sciences in general, has not fully been studied. This controversy could be partially solved if massive studies of empathy levels are made in similar cultural, social and economic contexts. Material and Methods:Empathy levels within the course were studied in eighteen dental schools from six countries in Latin America (2013). The mean of the empathy levels were used to study the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
(51 reference statements)
1
15
0
4
Order By: Relevance
“…However, some authors have found evidence that the empathic decline in students does not always occur; this has been found in various health careers (3,(9)(10)(18)(19)(20) . It has been suggested (21) that empathic decline is a particular case of various behaviors of means of empathy throughout courses or years of study, and that there is variability in this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors have found evidence that the empathic decline in students does not always occur; this has been found in various health careers (3,(9)(10)(18)(19)(20) . It has been suggested (21) that empathic decline is a particular case of various behaviors of means of empathy throughout courses or years of study, and that there is variability in this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…But, even if that were true in any case, it would be very complex and would require, before each intervention, studies of specific causes and the operation of their contribution to the process of decline. However, if it is indeed a particular case, and the evidence is consistent in this sense (18)(19)(20)(21) , then it is necessary to carry out exhaustive study of levels of empathy before developing any intervention processes, considering, in all cases, not only the study of empathy as a monolithic construct, but also of each of its components. The "simple fact" is that empathy is a dialectical synthesis of its three components.…”
Section: Discussionmentioning
confidence: 99%
“…‐ 7 For health care providers, having high levels of empathy increases their ability to understand the effect patients' experiences have on their illness, and better communication skills will translate into improved treatment outcomes 8, 9 . Health professionals who gained good communication skills and empathetic patient relationships have shown improved success in care provision 10, 11 …”
mentioning
confidence: 99%
“…On the other hand, differences have been found in the levels of empathy among students of different dental schools within a country, as well as differences among students from different countries (Díaz-Narváez, Erazo et al, 2017). In all these cases it is observed that the variables studied explain little about the behavior of the empathy.…”
Section: Discussionmentioning
confidence: 95%